The resolution of problems and their impact on the teaching of numerical thinking in 3rd grade students of the Yati Educational Institution (Docentes 2.0 Journal, 2019)
There resolutions of problems have been the subject of studies for years countless research highlights the importance of such competence for children’s learning in the teaching of mathematics. The teachers of the 21 st century continue calling us the need to rethink and carry out actions that focus on pedagogical weaknesses in the teaching of mathematics teaching processes, especially numerical thinking. In the educational Institution of Yati  de magangue´ - Colombia the resolution of mathematical problems is can academic difficulty ,the students’ performances in the this regard are low .the objective  of this study is to analyze how the resolution  of mathematical  problems affects the teaching of numerical thinking .to try to clarify this panorama , an investigation was initiated on the incidence of problem solving in the process of teaching numerical thinking in 3erd grade students. The study shows the great impact of the competence of problem solving in the teaching of numerical thinking and that its disuse by teachers in the planning and execution of classes remarkably influences the low performance of students in related content with numerical thinking.
Keywords: competence; numerical thinking; resolution of problems; teaching; learning